PEMANFAATAN LEMPUNG DESA GEMA TERAKTIVASI H2SO4 UNTUK PENINGKATAN MUTU MINYAK GORENG CURAH - Simanjuntak, Martha Sari; Muchtar, Akmal; Sophia, Halida (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Clay from Gema Village, Kampar Regency, Riau Province has been applied as an adsorbent. The increase of clay’s adsortive capacity can be done by modification. This study was aimed to use the activated clay to improve the quality of bulk cooking oil. The adsorbent preparation was began with activation process by using 0,5 M H2SO4, for 3 hours, and stirring rate 500 rpm. Activated clay showed the increase the intensity of quartz and montmorillonit, and accompanied by the loss of muscovite and kaolinite. The parameters that were used in this study were peroxide value, acid value, water content, odor, and colour. Adsorption process was observed in 7 gram activated clay with various contact time (30, 60, 90, and 120 minutes), the results then compared with SNI 3741:2013. The obtained result showed that the activated clay 0,5 M H2SO4 was able to decrease the acid value, and water content, respectively 54,55%, 48,75% with 120 minute and 7 gram weight of activated clay, it was also able to decrease peroxide value 39,64% with 60 minute and 7 gram weight of activated clay, and the color of bulk cooking oil was more clear, but it’s smells like clay.